Salmonella-Mediated Therapy Targeting Indoleamine 2, 3-Dioxygenase 1 (IDO) Activates Innate Immunity and Mitigates Colorectal Cancer Growth - Phan, Thuy (Cancer Gene Ther, 2019)
Patients with colon cancer remain largely refractory to current immunotherapeutic strategies. This is, in part, due to the overexpression of the immune checkpoint protein indoleamine 2,3-dioxygenase 1 (IDO). IDO is an important enzyme contributing to tumor-mediated immunosuppression and also correlates with poor prognosis in colon cancer patients. The aim of this study was to assess the therapeutic efficacy of attenuated Salmonella typhimurium delivering an shRNA plasmid targeting IDO (shIDO-ST) in two mouse models of colorectal cancer. In vitro, the CT26 and MC38 murine colon cancer cell lines were shown to upregulate IDO expression following stimulation with interferon-γ (IFN-γ) and tumor necrosis factor-α (TNF-α). Transfection of both cell lines with shIDO plasmid reduced IDO protein expression and function. In vivo, shIDO-ST treatment significantly delayed CT26 and MC38 tumor progression compared to mice treated with scrambled shRNA control (shScr-ST) or the clinically-tested IDO inhibitor epacadostat. Increased tumor infiltration of neutrophils was found to be the primary immune cell population associated with shIDO-ST treatment, suggesting robust activation of innate immunity. Although increased tumor expression of IDO is associated with resistance to antibody therapy against programed cell death-1 (anti-PD1), co-administration of anti-PD1 with shIDO-ST did not provide additional tumor growth control in either model of colorectal cancer. Altogether, we demonstrate that treatment with shIDO-ST markedly delays tumor growth in two immunocompetent colorectal mouse models and this appears to be a superior therapeutic strategy compared to epacadostat or blocking anti-PD1 antibody therapy in colon cancer.